2023
DOI: 10.3389/fimmu.2023.1263458
|View full text |Cite
|
Sign up to set email alerts
|

Active tuberculosis patients have high systemic IgG levels and B-cell fingerprinting, characterized by a reduced capacity to produce IFN-γ or IL-10 as a response to M.tb antigens

Julio Flores-Gonzalez,
Alexia Urbán-Solano,
Lucero A. Ramón-Luing
et al.

Abstract: IntroductionTuberculosis (TB) is a bacterial infection caused by Mycobacterium tuberculosis (M.tb). B cells are the central mediator of the humoral response; they are responsible for producing antibodies in addition to mediating other functions. The role of the cellular response during the TB spectrum by B cells is still controversial.MethodsIn this study, we evaluated the distribution of the circulating B cell subsets in patients with active and latent TB (ATB and LTB, respectively) and how they respond to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“… 30 Studies have reported increased IL-10 levels in TB patients, suggesting its role in the suppression of the protective immune response. 31 , 32 Our findings are consistent with these reports, demonstrating significantly higher IL-10 levels in SNPT patients compared to SPPT patients, with an AUC of 0.686. The chemokine CXCL8/IL-8 is linked to neutrophil recruitment and granuloma formation in TB.…”
Section: Discussionsupporting
confidence: 92%
“… 30 Studies have reported increased IL-10 levels in TB patients, suggesting its role in the suppression of the protective immune response. 31 , 32 Our findings are consistent with these reports, demonstrating significantly higher IL-10 levels in SNPT patients compared to SPPT patients, with an AUC of 0.686. The chemokine CXCL8/IL-8 is linked to neutrophil recruitment and granuloma formation in TB.…”
Section: Discussionsupporting
confidence: 92%